Folding laminar cover and water collector - Prototype - Simon Calle, Jaime Andrés (2019)
This research born as part of a efficient structural design and to address three different problems: the need to design a hedge that may adapt weather flexible spaces, the problematic to gather water in the coast of Perú due to the lack of it and finally that this options can be replicable and scalable along the world